Fundamentals of patent law : interpretation and scope of protection - Fisher, Matthew; Fisher, Matthew (Oxford ; Hart Publishing limited, 2007)
This new book provides a comprehensive overview of the topic of patent claim interpretation in the UK and in three other select jurisdictions
Includes bibliographical references (p. [393]-415) and index.
eng.
Keywords: Patent laws and legislation -- Great Britain; Patent laws and market economy